Pentingnya Moderasi Beragama dalam Pendidikan Islam: Studi Kasus di SMKS PEMBANGUNAN Rejang Lebong - Deti Ariani; Jumiati Indra Kusuma (GHAITSA : Islamic Education Journal, 2025)
Religious moderation is an approach that emphasizes the balance between exclusive religious experience and respect for the different religious beliefs and practices of others. This approach aims to avoid extremism, radicalization, and fanaticism in religion. Religious moderation is the key to creating tolerance and harmony between religious communities. This study analyzes the application of religious moderation in Islamic religious education at SMKS PEMBANGUNAN Rejang Lebong, using qualitative research methods involving interview and observation techniques. This study found that managerial management in the classroom plays an important role in the application of religious moderation. In the subject of Islamic Religious Education (PAI), religious moderation can be inserted through instilling an attitude of tolerance and concern for others. SMKS PEMBANGUNAN Rejang Lebong is an educational institution with ethnic, tribal, religious, and cultural diversity. This diversity opens up the potential for social conflict, so the application of the concept of religious moderation in Islamic education is very important to create harmony and social welfare in national and religious life.